Parasites as prey in aquatic food webs: implications for predator infection and parasite transmission. Issue 10 (25th April 2013) - Thieltges, David W.; Amundsen, Per‐Arne; Hechinger, Ryan F.; Johnson, Pieter T. J.; Lafferty, Kevin D.; Mouritsen, Kim N.; Preston, Daniel L.; Reise, Karsten; Zander, C. Dieter; Poulin, Robert
Abstract : While the recent inclusion of parasites into food‐web studies has highlighted the role of parasites as consumers, there is accumulating evidence that parasites can also serve as prey for predators. Here we investigated empirical patterns of predation on parasites and their relationships with parasite transmission in eight topological food webs representing marine and freshwater ecosystems. Within each food web, we examined links in the typical predator–prey sub web as well as the predator–parasite sub web, i.e. the quadrant of the food web indicating which predators eat parasites. Most predator– parasite links represented 'concomitant predation' (consumption and death of a parasite along with the prey/host; 58–72%), followed by 'trophic transmission' (predator feeds on infected prey and becomes infected; 8–32%) and predation on free‐living parasite life‐cycle stages (4–30%). Parasite life‐cycle stages had, on average, between 4.2 and 14.2 predators. Among the food webs, as predator richness increased, the number of links exploited by trophically transmitted parasites increased at about the same rate as did the number of links where these stages serve as prey. On the whole, our analyses suggest that predation on parasites has important consequences for both predators and parasites, and food web structure. Because our analysis is solely based on topological webs, determining the strength of these interactions is a promising avenue for future research.